Poland - Toward a Fiscal Framework for Growth : A Public Expenditure and Institutional Review - World Bank (Washington, DC, 2013)
The objective of this report is to assess the status of public expenditures, and develop recommendations to promote fiscal stability and growth in Poland, towards the consolidation and restructuring of its public finances, strengthening its budget management, and better leverage in EU financing. This report examines those social and structural reform issues that affect, or are affected by the stance of public finance. First, it reviews Poland's economic performance with a focus on its macroeconomic policy mix, public debt sustainability issues, and developments in public finance, and expenditure composition. It highlights the need to tighten fiscal policy as a means to further rebalance the macroeconomic policy mix, and to reverse unfavorable debt dynamics. It also points out that Poland's public sector is relatively large for its income level, and that social protection and assistance related expenditures have been a major source of this situation. In particular, investment in physical infrastructure has been relatively neglected during the last decade in favor of expenditures on social programs and consumption. Fiscal consolidation has also been hampered by over-indexation of social expenditures. Second, the report examines the extent to which the current budgetary outcomes are the result of weaknesses in the incentive arrangements for good budgeting. The report suggests significant reforms in budget processes for sustainable improvements in public finances, in particular, priority areas include measures to consolidate the budget, to ensure a comprehensive picture of public finances, and effective cash management; to strengthen budgetary processes by exercising a Medium-Term Expenditure Framework, and incentives for improved public service delivery; and, to strengthen ex-post internal and external audit systems. Third, the report examines options for expenditure cuts and restructuring, necessary for fiscal sustainability, in particular, it discusses those sectoral programs that could potentially: (i) provide significant savings to the budget (social protection); (ii) contribute to Poland's human and physical capital; (iii) unlock the growth potential of underutilized factors of production in agriculture and Poland's rural areas; and, (iv) improve the country's living conditions, by upgrading its environmental standards as agreed with the EU.